ANALISIS KEGIATAN MARKET DAY UNTUK MENINGKATKAN PEMAHAMAN NILAI MATA UANG PADA ANAK USIA DINI - Lena bunga lestari; Salwa fadita; Frida Ayu (CV. Denasya Smart Publisher, 2024)
A young child is a golden age a golden opportunity, and yet, teaching entrepreneurship atan early age is not an easy thing to do. Whereas on the other hand, introducing an early entrepreneurial spirit is an important investment in their development. This will help them in developing skills such as innovation, leadership, and ability to overcome challenges that can be particularly valuable in their later lives. In introducing early entrepreneurship to children, it is required in a pleasant and educational way. Introducing entrepreneurship in young children not only helps them understand the business world but also develops their skills such as creativity, problem solving, and confidence. Market day is one of the efforts to build and encourage the entrepreneurial ship or entrepreneurship in young children atan early age. In this study, it uses descriptive qualitative methods. Inside market day activities, children acquire the learning process firsthand. Children do learning by doing or learn by direct performance. Thus young children can experience firsthand how to create innovation, create, and marketing effective for their products and know what they need when they want to become entrepreneurs.